Asymmetric and intermittent supershear rupture mediated by local fault complexity during the 2025 M W 7.7 Myanmar earthquake - Tao Xia; Lingling Ye; Jinlai Hao; Haijun Gao; Thorne Lay; Xiaotian Ding; Zhenxing Yao (Proceedings of the National Academy of Sciences, 2026)
We determine the detailed rupture process of the 2025 M W 7.7 Myanmar earthquake by joint inversion of near-fault strong-motion, geodetic, and teleseismic data. The rupture initiated with significant slip of up to ~5 m near the epicenter. Localized fault geometric complexity and stress heterogeneity might have led to small-scale slip segmentation and intermittent episodes of supershear rupture. Northward rupture propagation was subshear overall and terminated rapidly after extending ~80 km within the partial stress shadow of a 2012 earthquake. In contrast, southward rupture propagated ~380 km, fully traversing a predefined seismic gap that had been unruptured since 1839, and undergoing cycles of acceleration and deceleration that included at least two episodes of intermittent supershear rupture before gradually stopping after traversing a segment that ruptured in 1930. Slip exceeding 3 m is confined to the shallow fault above a 15 km locking depth and the average static stress drop is 4.7 MPa. The long-term stress accumulation on multiple asperities along the central Sagaing fault promotes localized ruptures in discrete events but sometimes leads to rupture cascades with intermittent supershear behavior as in 2025. Local slip duration also displays a north–south asymmetry, being longer near the epicenter and progressively shorter toward the south before the end. This pattern may be associated with lower rigidity near the epicenter and rupture dynamics being modulated by fault edges for long, narrow strike-slip faults. Our findings highlight the roles of localized fault structure and stress heterogeneity in controlling slip distribution and rupture speed.